DEALING WITH CULTURE CLASHES IN A GLOBALIZED WORLD ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
In a globalized society, culture clashes are increasingly common due to frequent interactions between people from diverse backgrounds. These clashes can result in misunderstandings and conflicts if not managed properly. This thesis explores the causes and consequences of culture clashes, emphasizing the role of cultural intelligence, communication strategies, and education in resolving them. Real-world examples and academic references are used to support the discussion, highlighting the importance of empathy, openness, and intercultural competence in fostering mutual understanding.